Expression of the human calcitonin/CGRP gene in lung and thyroid carcinoma - Edbrooke, M.R.; Parker, D.; McVey, J.H.; Riley, J.H.; Sorenson, G.D.; Pettengill, O.S.; Craig, R.K. (The EMBO journal, 1985)
Nucleotide sequence analysis of a partially processed polyadenylated precursor RNA transcript shows that the human calcitonin gene in common with the rat calcitonin gene, encodes calcitonin and the calcitonin gene related peptide (CGRP). Using hybridisation probes specific to calcitonin mRNA, intron, coding and non‐coding regions of the CGRP mRNA, we demonstrate by Southern blotting the existence of a second human CGRP gene, and by RNA blotting and S1 mapping, the differential expression of calcitonin and CGRP in medullary thyroid carcinoma and human lung tumour cell‐lines. These studies implicate the requirement for separate post‐transcriptional events in the differential expression of calcitonin and CGRP from a single gene, the preferential use of splice acceptor sites for the synthesis of CGRP mRNA, and post‐transcriptional cleavage modulated by a trans‐acting gene product for the synthesis of calcitonin mRNA. Studies using antisera raised against CGRP and calcitonin, demonstrate elevated circulating levels of plasma CGRP in medullary thyroid carcinoma which do not parallel calcitonin levels, and the presence of CGRP in secretions from lung tumour cell‐lines. These studies indicate that CGRP is a tumour marker of diagnostic and possibly prognostic value in the management of lung and thyroid tumours.